El lugar común en la construcción e interpretación del texto publicitario - Corrales Crespo, Pedro R. (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Clichés in advertisement have a text-creating function as well as an argumentative one, i.e., they are a construction tool that guides text interpretation, as shown by means of the analysis of a press ad for a whisky brand, in a modified relevance theoric framework where the speaker forces the reader into a specific interpretation.